Photo-identification of individual rainbow trout, Oncorhynchus mykiss (Actinopterygii, Salmoniformes, Salmonidae), using the flank spot pattern - Nelson Colihueque; Francisco Estay (Acta Ichthyologica et Piscatoria)
The flank skin spot patterns for identification of rainbow trout individuals may be useful as an alternative non-invasive tagging method for addressing biological questions related to this species, including issues relevant to fish farming. This approach has potential because the spot arrangement is usually specific to each individual. In this study, we analyzed the flank spot patterns of individuals from two rainbow trout Oncorhynchus mykiss (Walbaum, 1792) populations—one naturalized population (n = 56, Calafquén Lake, Región de La Araucanía) and one farmed population (n = 45, Piscícola Huililco Ltd., Región de La Araucanía)—to evaluate whether these spot patterns are useful for the photo-identification of fish. The flanks of the individuals were photographed with a digital camera. Then, the spot pattern of each image was annotated with freely available software (Interactive Individual Identification System, I3S) to evaluate the performance of these patterns in identifying individuals based on a ranking image score where each image was compared with all annotated images stored in an identification database. Spot patterns for long-term identification were also evaluated using a subset of images from the farmed population. The use of spot patterns showed a high performance for the identification of individuals, because in both populations, all annotated images ranked the first ranking score, indicating perfect recognition. The long-term analysis revealed a high performance in recognition of individuals because 75% of the images of fish at the age of 2 years were successfully matched with images of the same fish at the age of 3 years.